(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Teaching Russian to foreigners: the role of non-verbal means of communication The problem of studying the role of non-verbal means of communication in the process of teaching foreign students. Nonverbal communication side, despite its importance in the transmission of information, often remains out of view of the person, even though we intuitively know that no interaction takes place without their participation. Knowledge of etiquette and cultural differences, especially non-verbal behavior of the Russian people creates the necessary conditions for effective mastering the Russian language members of a linguistic community. The article deals with the ways and means of using gestures, facial expressions, body movements during speech production, in «playing the social roles», in playing mikrostsen at Russian lessons. Particular attention is paid to active minimal gestural-mimic means assimilation of which is a basic requirement in shaping lingvostranovedcheskogo competence of future specialists. The article concludes that the inclusion of all the necessary conditions for the effective use of non-verbal means of communication leads to the full mastery of the language